2002
DOI: 10.1046/j.0016-8025.2001.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall‐associated isoflavonoids andβ‐glucosidase activity inLupinus albusplants responding to environmental stimuli

Abstract: Plants respond to various biotic or abiotic stimuli with different mechanisms and the mobilization of phenolic compounds is one of them. In white lupin ( Lupinus albus L.) plants, isoflavones and their glucosides were localized in cell walls where the high constitutive activity of β β β β -glucosidase (EC 3·2·1·21) was also identified. The enzyme was partially purified from root cell walls. Its polymeric active form has 180 or 200 kDa as determined by non-denaturing electrophoresis and gel filtration, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…The content of all identified isoflavones increased in all stress-treated samples, which confirms previously published data [26,33,37,38]. Wu [39] demonstrated that soybean isoflavones show free radical scavenging potential, with aglycones (daidzein and genistein) being stronger scavengers than their glycoside conjugates (daizdin and genistin).…”
Section: Figsupporting
confidence: 77%
“…The content of all identified isoflavones increased in all stress-treated samples, which confirms previously published data [26,33,37,38]. Wu [39] demonstrated that soybean isoflavones show free radical scavenging potential, with aglycones (daidzein and genistein) being stronger scavengers than their glycoside conjugates (daizdin and genistin).…”
Section: Figsupporting
confidence: 77%
“…To date, there are several reports of studies of flavonoid-glucoside in the root (Shibuya et al 1991). In addition, conjugated flavonoid-glucosidase activity was reported in lupin root (Pislewska et al 2002). However, these reports are of root nodule plants.…”
Section: Organ Distribution Of Rutin and F3g Activity In 4 Dag Seedlingmentioning
confidence: 94%
“…G2 preferred isoflavonoid over flavonoid glucosides, and G4, with a broad substrate preference, was down-regulated by YE. Other ␤-glucosidases have been shown to exhibit preference for specific (iso)flavonoid compounds, such as a set of chickpea isoenzymes possessing K m values for isoflavones of at least 100-fold lower than for other phenolic glycosides (34), enzymes from white lupin roots that, like the Medicago enzymes, can cleave isoflavone glucosides but not kaempferol 3-O-␤-glucoside (35), and an enzyme from soybean roots (GmICHG) that has very high specificity and turnover for gensitein and daidzein malonyl glucosides (36). This enzyme is found in the cell wall fraction in soybean roots, and, of the Medicago enzymes reported here, is most closely related to G2 (70% at the amino acid level) (SI Fig.…”
Section: Discussionmentioning
confidence: 99%